2000
DOI: 10.1097/00001648-200005000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Myelodysplastic Syndromes

Abstract: The purpose of this case-control study was to investigate tobacco smoking as a risk factor for myelodysplastic syndromes, emphasizing karyotypic aberrations as markers for exposure and risk differentiation with respect to morphology. We obtained smoking history by interview of 330 cytogenetically investigated adult myelodysplastic syndrome cases and 337 controls, matched with respect to sex, year of birth, and county of living. Smoking for at least 1 year at some time 20 years or less before diagnosis was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 20 publications
1
35
1
1
Order By: Relevance
“…19 Our data also showed that the increased risk associated with smoking started to decline 5 years after smoking cessation, yet remained a significant risk factor until 15 years after smoking cessation. These data suggest that smoking could have a longer effect in MDS development than the 5 years suggested by Bjork et al 17 The role of overall alcohol consumption on risk of MDS has been explored in a few studies with conflicting results. 9,14,20,21 In the present study, we had the opportunity to analyze the effect of specific alcoholic beverages.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…19 Our data also showed that the increased risk associated with smoking started to decline 5 years after smoking cessation, yet remained a significant risk factor until 15 years after smoking cessation. These data suggest that smoking could have a longer effect in MDS development than the 5 years suggested by Bjork et al 17 The role of overall alcohol consumption on risk of MDS has been explored in a few studies with conflicting results. 9,14,20,21 In the present study, we had the opportunity to analyze the effect of specific alcoholic beverages.…”
Section: Discussionmentioning
confidence: 91%
“…The only large study that analyzed smoking by FAB type found an association only with the RARS type. 17 This difference could be due to the difference in the study populations. Tobacco is the major source of nonoccupational benzene, and a higher concentration of benzene has been found in the urine of smokers than in nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been studied thoroughly as a risk factor for myelodysplasia in many studies. Most of them revealed a significant association of smoking with MDS [9,25,28,29,30], whereas others did not [8,13,27]. A meta-analysis confirmed that smoking plays an important role in the occurrence of MDS [32].…”
Section: Discussionmentioning
confidence: 99%
“…These genetic abnormalities occur due to previous exposure to mutagens like benzene, alkylating agents, gasoline, topoisomerase II inhibitors, radiation etc. [7][8][9][10][11][12][13]. Due to exposure to insecticides, pesticides and herbicides agricultural workers are reported to have higher incidence of developing MDS [7].…”
Section: Introductionmentioning
confidence: 99%